A Reflection of Kinship Between Indonesian and South Patani Malay Languages: Homophone and Homograph - Fakhriyyah Asmay Aidha; Muyassaroh Muyassaroh; Lavatee Chite (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
The study aims to identify and describe the kinship of the words between Indonesian and South Patani Malay languages. Indonesian and South Thai Patani are the languages in the large family of Austronesian. Vocabulary mastery was the skill one possessed in understanding DNA by using the set of words in a language to match the meaning. The similarities between the Indonesian and the South Patani Malay languages made the students from South Thai Patani mistakes in speech and writing. The study used a qualitative descriptive method that was used to analyze the homophone and homograph words in a conversation between Indonesia and South Patani students on writing notes and verbal technique by Padan method. The data are collected from text messages and screenshot pictures on the Rumah Nusantara online forum in the Messenger application regarding communication between native speakers and Patani Thailand students by listening and taking notes technique. Data analyses in this research based on means of words structures every word in a reflection of kinship homophone and homograph within the translational method by way of language-deciding devices have kinship or not. Data processing in this research utilizes switching conversation messages between both students (native speakers and foreign), who are Indonesian and South Patani students. The study has led to the discovery of language kinship by homophone and homograph words. The number of data found was 25 data out of 8 homophone words and 17 homograph words. In conclusion, both languages have a similar kinship of forebear lineage based on homophone and homograph words, which has been found in the phonetic and orthographic aspects scheme of the relationship in the linguistics family.